OPENING STRUCTURE OF THE BONE BASIN ON SOUTH SULAWESI IN RELATION TO PROCESS OF SEDIMENTATION - Lili Sarmili (Marine Geological Institute of Indonesia, 2015)
Sulawesi Island is situated on the three major plates, namely the Indo-Australian plate together with Continent Australia (Australian Craton) plate moves towards the North - Northeast and crust Pacific - Philippines moves towards the West - Northwest, causing the collision with the Eurasian plate (Sunda Land) which more passive or stable. The Bone basin is located between South Sulawesi and Southeast Sulawesi arms. This basin is formed by several fault system, such as, Walanae, Palukoro, West and East Bone faults and others. Several active faults are likely to be extended each other into the openings structure and characterized by the accumulation of young sediment in the Bone basin. Keywords: Sulawesi, collision Bone basin, faults, sedimentation Pulau Sulawesi merupakan tempat pertemuan antara tiga lempeng besar, yaitu lempeng Indo-Australia bersama-sama dengan lempeng Benua Australia (Australian Craton) bergerak ke arah Utara - Timurlaut dan Kerak Pasifik - Filipina bergerak ke arah Barat - Baratlaut sehingga terjadi tumbukan dengan lempeng Eurasia (Daratan Sunda) lebih bersifat pasif atau diam. Secara geologi Cekungan Bone terletak diantara Lengan Sulawesi Selatan dan Lengan Sulawesi Tenggara. Cekungan ini terbentuk oleh beberapa sistem sesar yaitu sesar Walanae, Palukoro, Timur dan Barat Bone dan lainnya. Beberapa sesar aktif tersebut kemungkinannya saling tarik menarik menjadi struktur bukaan dan ditandai dengan adanya akumulasi sedimentasi muda di cekungan Bone. Kata kunci: Sulawesi, tumbukan, Cekungan Bone, Sesar, Sedimentasi